2017
DOI: 10.1136/thoraxjnl-2016-209671
|View full text |Cite
|
Sign up to set email alerts
|

The use of pretest probability increases the value of high-resolution CT in diagnosing usual interstitial pneumonia

Abstract: Background Recent studies have suggested that non-definitive patterns on high-resolution CT (HRCT) scan provide sufficient diagnostic specificity to forgo surgical lung biopsy in the diagnosis of idiopathic pulmonary fibrosis (IPF). The objective of this study was to determine test characteristics of non-definitive HRCT patterns for identifying histopathological usual interstitial pneumonia (UIP). Methods Patients with biopsy-proven interstitial lung disease (ILD) and non-definitive HRCT scans were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 20 publications
5
70
0
11
Order By: Relevance
“…Previous studies have shown that patients with histologically proven IPF can present without the typical CT findings of UIP. 30 With the availability of new antifibrotic drugs such as pirfenidone and nintendanib 31,32 that slow down disease progression, treatment response needs to be measured. However, the most commonly used FIGURE 4.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients with histologically proven IPF can present without the typical CT findings of UIP. 30 With the availability of new antifibrotic drugs such as pirfenidone and nintendanib 31,32 that slow down disease progression, treatment response needs to be measured. However, the most commonly used FIGURE 4.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of patient populations meeting the "probable UIP" criteria in high-resolution computed tomography (HRCT) indicate that lack of honeycombing should not exclude IPF diagnosis if all remaining radiographic features of the UIP pattern are present (especially predominantly subpleural and basal distribution of changes as well as the presence of bronchiectasis) [30,[88][89][90][91][92][93][94][95][96][97][98]. The extent of reticular changes is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published meta-analysis demonstrated that IPF diagnosis can be made in as many as 94% (87-99%) of patients with a radiographic pattern corresponding to "probable UIP" [100]. The probability of IPF diagnosis increases in an appropriate clinical context, comprising the following: age above 60 years, a positive history of tobacco smoking (currently or in the past) and lack of other identifiable causes that could lead to interstitial fibrosis (especially lack of significant environmental exposure, chronic use of potentially pneumotoxic drugs or signs of CTD) [31,97,99,101,102]. In the group of patients with "probable UIP" (who had not undergone lung biopsy), an annual FVC decline was observed as well as a response to antifibrotic treatment (with nintedanib) reducing the rate of this decline, comparable with outcomes observed in the "definite UIP" group (based on radiographic or pathomorphological presentation) [103].…”
Section: Introductionmentioning
confidence: 99%
“…HRCT may be used to identify sites for bronchoalveolar lavage and lung biopsy, guide treatment strategies, and predict treatment outcomes [6].…”
Section: Introductionmentioning
confidence: 99%